Socio-economic and ecological factors linked to the adoption of foreign livestock breeds by Zimbabwean smallholders farmers in the Great Limpopo Transfrontier Conservation Area - Chiedza R. Mudavanhu; Prisca H. Mugabe; Venancio H. Imbayarwo-Chikosi; Billy Mukamuri; Alexandre Caron (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux)
Background: In rural areas in Africa, the productivity of small-scale livestock systems is low. Development programmes aim to increase productivity using technical innovations, including the introduction of foreign breeds. The level of adoption of foreign breeds needs to be investigated to assess the effectiveness of the introduction programmes. Aim: This article analyzes the socio-economic and ecological factors associated with the adoption of foreign livestock breeds in Zimbabwean rural communities, in the Great Limpopo Transfrontier Conservation Area. The foreign breeds concerned, include Brahman cattle, Boer goats and Boschveld chickens. Methods: A mixed methodology was used, combining a literature review, individual in-depth interviews (n=100), key-informant interviews and focus group discussions. Triangulation and thematic analysis informed both research and data analyses. Results: The key socio-economic dynamics that influence the perceptions and adoption of specific livestock breeds were linked to productivity, reproduction, management, social criteria and health. The most important ecological factors included livestock predation, heat stress, and shortages of water and pasture. Despite the productive potential of foreign breeds, the level of adoption was low due to the local context, in which foreign breeds were unable to express their full genetic potential. Most farmers keep indigenous breeds because they are well adapted to local climatic conditions and resistant to livestock diseases. Conclusions: To improve the effectiveness of programmes targeting livestock production, governmental services and development, stakeholders should adopt more participatory processes and adaptive management strategies, which better reflect smallholders’ demands.